Physiological Modulation Approaches to Improve Cancer Chemotherapy : A Review - Kumar, Rajesh; Kaur, Maninder; Silakari, Om (Anti-Cancer Agents in Medicinal Chemistry, 2014)
The success of anticancer therapy is limited due to the resistance caused by tumor cells to cytotoxic agents, which interfere with the effectiveness of various chemotherapeutic agents. Several mechanisms for decreased effectiveness of anti-cancer drugs have been examined however the most widely studied mechanism is the efflux of cytotoxic drugs from the cell due to P-gp overexpression. However, the role of P-gp inhibitors in improving chemotherapy is limited due to the existence of other mechanisms of resistance such as activation of glutathione mediated detoxification, blockade of DNA repair, apoptotic pathways, TK signaling pathways and altered tumor microenvironment. Alternative strategies to overcome factors responsible for reduced efficacy of cancer therapy have also been considered such as inhibition of the detoxification system like glutathione, targeting Tks and DNA repair pathways, combination of angiogenic inhibitors, RNAi mediated inhibition of targeted genes etc. Additionally, preventing the onset of resistance can be targeted via siRNA strategy and nanoparticle strategy. In this review, we describe detailed mechanisms involved in decreasing effectiveness of anticancer drugs as well as the strategies used to modulate these mechanisms for effective cancer treatment.
Keywords: cancer